Models, monitoring, and the mind: Comments on Wansink and Chandon's "Slim by Design". Issue 3 (12th March 2014) - Herman, C. Peter; Polivy, Janet
Abstract: Wansink and Chandon have examined the "mindlessness" that is often evident in everyday food intake. In this commentary, we focus on four issues raised by Wansink and Chandon's paper: (1) the distinction between food choice and food intake; (2) their model of food intake (and how it compares and contrasts with our own model of food intake); (3) the role of monitoring in the control of food intake; and (4) the meaning of "mindless" eating. In each case we find value in Wansink and Chandon's proposals but also an opportunity for further analysis and refinement.